The brave new social media - Amon Prodnik, Jernej (Teorija in praksa, 2014)
The paper looks at the wider role of information and communication technologies (ICTs) in the context of their use in global political struggles, but also on the back of their sweeping abuse for surveillance by global capitalist corporations and state institutions. A general question is raised: can the Internet and social media be perceived as a means of social progress or as mechanisms of oppression? The author proceeds from a critical perspective and emphasises that ICTs must be analysed as parts of the social totality. They cannot be understood in a dichotomous way, but only as being full of contradictions. Yet, contradictions do not entail relativism - class inequalities, exploitation and domination are filtered through ICTs together with the manifold antagonisms emerging from capitalist societies.
Keywords: Communication; Družbeni mediji; informacijsko-komunikacijska tehnologija; information and communications technology; Internet; Komuniciranje; Political economy; Politična ekonomija; Social media